Hubungan Antara Perilaku Penggunaan Pestisida dengan Kejadian Anemia pada Petani di Desa Candirejo - Sri Lestari; Alfan Afandi; Annisa Putri Heryanda; Avida Noor Hidayah (Universitas Ngudi Waluyo, 2024)
The use of pesticides is carried out by farmers as an effort to control pests and plant diseases. The use of pesticides in agriculture can improve the quality and quantity of crops produced. Long-term exposure to pesticides can increase the risk of chronic health problems. Pesticides contain strong chemicals that, if continuously exposed, can interfere with the production of red blood cells in the body. Pesticides that enter the human body can cause poisoning and various health problems, one of which is anemia. The purpose of this study was to determine the relationship between pesticide use behavior and the incidence of anemia among farmers in Candirejo Village. This research is quantitative with cross sectional design. The population used was all farmers in Candirejo Village with a sample of 30 respondents, taken using purposive sampling technique. Data were collected by questionnaire and Easy Touch GCHb, analyzed using Chi Square test and Fisher's Exact test. The results of the analysis showed that there was a relationship between the use of PPE and anemia (p=0.001), there was no relationship between the frequency of spraying and anemia (p=0.300), there was no relationship between the length of spraying and anemia (p=0.439) and there was no relationship between spraying time and anemia (p=0.682). There is a relationship between the use of PPE and the incidence of anemia and there is no relationship between the frequency, duration and time of spraying with anemia.' ABSTRAK Penggunaan pestisida dilakukan oleh petani sebagai upaya mengendalikan hama dan penyakit tanaman. Pemakaian pestisida pada pertanian dapat meningkatkan kualitas maupun kuantitas tanaman yang dihasilkan. Paparan jangka panjang terhadap pestisida dapat meingkatkan risiko terjadinya gangguan kesehatan kronis. Pestisida mengandung bahan kimia yang kuat, jika terpapar terus-menerus, dapat mengganggu produksi sel darah merah dalam tubuh. Pestisida yang masuk ke dalam tubuh manusia dapat menyebabkan keracunan dan berbagai gangguan kesehatan, salah satunya adalah anemia. Tujuan penelitian ini adalah untuk mengetahui hubungan antara perilaku penggunaan pestisida dengan kejadian anemia pada petani di Desa Candirejo. Penelitian ini adalah kuantitatif dengan rancangan cross sectional. Populasi yang digunakan adalah seluruh petani di Desa Candirejo dengan sampel sebanyak 30 responden diambil menggunakan teknik purposive sampling. Data dikumpulkan dengan kuesioner dan Easy Touch GCHb, dianalisis menggunakan uji Chi Square dan uji Fisher’s Exact. Hasil analisis menunjukkan ada hubungan antara penggunaan APD dengan anemia (p=0,001), tidak ada hubungan antara frekuensi penyemprotan dengan anemia (p=0,300), tidak ada hubungan antara lama penyemprotan dengan anemia (p=0,439) dan tidak ada hubungan antara waktu penyemprotan dengan anemia (p=0,682). ada hubungan antara penggunaan APD dengan kejadian anemia serta tidak ada hubungan antara frekuensi, lama dan waktu penyemprotan dengan anemia.